Representasi Bahasa Generasi Z pada Konten Kreator Fujian Utami Putri di Media Sosial - Adinda Atiqotuz Zummah; Magfirotul Hamdiah (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study aims to describe the form and sociolinguistic function of Generation Z language representation used by content creator Fujianti Utami Putri on social media. A descriptive qualitative approach with content analysis method was applied to dissect this linguistic phenomenon deeply. The data source consists of an audio-visual document from a single video titled